Leishmanioses do continente americano (SciELO - Editora FIOCRUZ, 2014)
In Brazil, it was already responsible for epidemics in different cities. In the last ten years, its lethality has increased in several regions of the country. In various parts of the world it has been expanding, including in places where previously there was no transmission record. Infection by parasites of the Leishmania genus causes one of the most neglected tropical diseases today. It is estimated that there are 350 million people at risk of contracting the infection, especially in the poorest areas of the planet, and that two million new cases of leishmaniasis occur each year. This serious scenario justifies the effort undertaken by the organizers and other researchers at the Oswaldo Cruz Institute (IOC/Fiocruz) who are experts on the subject, as well as by professionals from other Fiocruz units and Brazilian institutions: they have prepared a collection that compiles existing knowledge about the subject, identifies the main challenges and discusses strategies to face them.